The SCREENING OF SIX GRAPEVINE VARIETIES FROM FRANCE IN NURSERY FOR THEIR RESILIENCE TO THE PEDOCLIMATIC CONDITIONS OF COTE D’IVOIRE: Adaptation of the grapevine in Côte - KOUAKOU, Tanoh Hilaire; Lucien, GOGBEU Dan Gbongué; Samuel, KOUADIO Oi Kouadio; Hilaire, KOUAKOU Tanoh (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2022)
The obvious interest of Africans for the culture of the grapevine and in particular in Côte d’Ivoire, has only increased in recent years. In this context, grapevines from France have been investigated in nursery in the aim to find varieties resilient to the pedoclimatic conditions of Côte d’Ivoire, to develop its culture. To this purpose, cuttings of six grapevine varieties namely Aleatico, Béquignol, Muscat rouge, Italia blanc, Sulima blanc and Exalta blanc, were put in nursery in polyethylene bags containing a mixture of arable soil from the experimental plot of the University Nangui Abrougoua (Abidjan-Côte d’Ivoire) and of compost made from local debris. Two-weekly after sowing the cuttings, the hardiness of the developed grapevines was evaluated through some morpho-physiological parameters. The screening revealed that three varieties, which are Bequignol, Muscat rouge and Aleatico, presented good morpho-physiological profiles. These varieties seem to adapt to the soil and climate conditions of Côte d’Ivoire. On the other hand, the varieties Exalta white, Italia white and Sulima white did not perform well in the nursery. Indeed, a deleterious effect of the substrate was observed on the morpho-physiological parameters of these varieties, showing their non-adaptation to the pedological and climatic conditions of the region of Abidjan, representing the sampled zone in Côte d’Ivoire. Thus, it is possible to test the culture in planta o